Dynamics of farmer-herder conflicts in Africa - Flintan, Fiona E.; Sulieman, Hussein; Eba, Bedasa; Nassef, Magda (DLG-Verlag GmbH, 2024)
Farmer-herder conflicts in Africa are receiving increased attention together with concerns over increasing and intensifying tension between the two groups. However, the question arises whether such concerns are really justified. A review of the literature suggests that there is indeed sparse robust evidence of such claims. This article presents the results of a systematic scoping literature review from the last two decades on that topic and develops a framework with concrete recommendations for future research.